3-D Microstructure Reconstruction of Tetragonal Zirconia Polycrystalline - Grabowski, Grzegorz (Journal of Casting & Materials Engineering, 2025)
The microstructure of a material is fundamental to its properties and behavior under mechanical and thermal loads. Understanding the internal structure of a material and controlling the microstructure at the stage of ceramic materials synthesis are essential for designing materials with desired properties. This study focuses on the three-dimensional reconstruction of the microstructure of yttria-stabilized tetragonal zirconia polycrystalline (TZP). The goal was to create accurate digital models of the microstructure, which could be used for further material analysis. The study utilized images obtained through scanning electron microscopy (SEM), based on which the basic stereological parameters were determined. The microstructure reconstruction was performed using the Laguerre tessellation method, allowing for the generation of three-dimensional digital models of the microstructure that represent the material’s internal structure. The results confirm that based on the basic stereological parameters obtained from two-dimensional cross-sections, three-dimensional reconstruction of the microstructure of polycrystalline zirconia is possible. This work, therefore, represents a step towards the effective design of ceramic materials with high performance parameters, through the control and optimization of their microstructure.